Identidades e relações de gênero em movimentos no território dos Cocais-PI. - LIMA, Jascira da Silva (2018)
The present study aims to problematize the forms of identity manifestations of women, especially the extractivist of babaçu, triggered in the conflicts surrounding the struggle for free babaçu, and the differences and inequalities in gender relations in spaces and spheres The Cocais Territorial Council, the Intersectoral Movement of Babaçu Coco Breakers - MIQCB and the Women's Committee. The empirical reality observed was the Cocais Territory, in the state of Piauí, during the process of implementation of the National Plan for Sustainable Rural Development and Solidarity - PNDRSS, started in 2010. This chosen for having the performance of the three spheres of government and new Social movements, highlighting the work of the Ministry of Agrarian Development (MDA) and the Special Advisory Office on Gender, Race and Ethnicity (AEGRE), as the main interlocutors of the government, and the Feminist Center March 8, as the interlocutor for the women's movement in the debate on gender and public policies. There are conflicts of interest, opinions and perspectives that demand a differentiated dynamic for the processes of discussions, negotiations, prioritization and implementation of actions and projects for the rural environment. In this same environment are observed and problematized the gender differences that reproduce forms of subordination and violence against women, as well as their strategies of organization and political participation in public spheres of power as a way of coping with inequality and social exclusion. For the reflexive analysis of the tensions around gender identity and relations in movements, I have used the theoretical contribution of the poststructuralist strand of thought, since, in general, the authors of this current of thought, such as Stuart HALL (2011), Joan SCOTT (1995), Judith Butler (2003) are those who reject definitions that contain absolute truths about the world. For them, and for me, the truth would depend on the historical context of each individual, which allowed me to treat the experience of women as a social construction in a constant process of change.